2013
DOI: 10.3390/md11125051
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Four New agr Quorum Sensing-Interfering Cyclodepsipeptides from a Marine Photobacterium

Abstract: During our search for new natural products from the marine environment, we discovered a wide range of cyclic peptides from a marine Photobacterium, closely related to P. halotolerans. The chemical fingerprint of the bacterium showed primarily non-ribosomal peptide synthetase (NRPS)-like compounds, including the known pyrrothine antibiotic holomycin and a wide range of peptides, from diketopiperazines to cyclodepsipeptides of 500–900 Da. Purification of components from the pellet fraction led to the isolation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 21 publications
(37 reference statements)
0
30
0
Order By: Relevance
“…Secondary metabolites are thought to play several roles in nature, such as antagonism, inter- and/or intraspecies communication, and stress response. We speculate that the well-known antibacterial compounds holomycin (34) and andrimid (35) may serve to antagonize competitors and that the quorum-sensing-interfering molecules solonamides and ngercheumicins may be involved in intercellular communication since they can interfere with the quorum-sensing system of Staphylococcus aureus (36, 37); however, the elucidation of the exact function of the secondary metabolites identified in this work during chitin colonization requires further work. With regard to the transcriptional regulation of the biosynthesis of secondary metabolites, the upregulation of the andrimid biosynthetic genes and of the LysR family transcriptional regulator located just downstream of them supports the hypothesis that such a regulator may have an important regulatory role in andrimid biosynthesis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolites are thought to play several roles in nature, such as antagonism, inter- and/or intraspecies communication, and stress response. We speculate that the well-known antibacterial compounds holomycin (34) and andrimid (35) may serve to antagonize competitors and that the quorum-sensing-interfering molecules solonamides and ngercheumicins may be involved in intercellular communication since they can interfere with the quorum-sensing system of Staphylococcus aureus (36, 37); however, the elucidation of the exact function of the secondary metabolites identified in this work during chitin colonization requires further work. With regard to the transcriptional regulation of the biosynthesis of secondary metabolites, the upregulation of the andrimid biosynthetic genes and of the LysR family transcriptional regulator located just downstream of them supports the hypothesis that such a regulator may have an important regulatory role in andrimid biosynthesis (38).…”
Section: Discussionmentioning
confidence: 99%
“…During rescreening, only 39 strains retained their antagonistic activity (18). We isolated the potent antibiotics holomycin and andrimid from Vibrio coralliilyticus and Photobacterium galatheae, respectively (9,18), as well as modulators of virulence in Staphylococcus aureus, such as ngercheumicins F, G, H, and I (19), nigribactin (20), and solonamide B (21). However, we were challenged by the marked reduction in bioactivity during rescreening.…”
mentioning
confidence: 99%
“…Singh et al binding activity at the P3 site in the MRSA strain USA300. Screening natural QSIs using more than five hundred marine bacterial strains identified six novel cyclodepsipeptides from the marine Gramnegative bacterium Photobacterium, solonamide A/B and ngercheumicins (F, G, H, and I), as agr QS inhibitors (Mansson et al 2011;Kjaerulff et al 2013). Furthermore, the study demonstrated that the compound directly bound to AgrA and prevented the interaction of AgrA with the agr P2 promoter.…”
Section: Zbzl-yaa5911 Targeting Fsrmentioning
confidence: 99%